2016
DOI: 10.1039/c6tc03218d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of single crystalline In2O3 octahedra for the selective detection of NO2 and H2 at trace levels

Abstract: Selective detection of oxidising or reducing species is achieved via selecting operating temperatures and metal loading of single crystalline In2O3 octahedra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…When operated at the optimal operating temperature of 150 °C, response and recovery times (t90) for nitrogen dioxide were 105 and 785 s, respectively. These are very similar to the values reported in [6]. …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…When operated at the optimal operating temperature of 150 °C, response and recovery times (t90) for nitrogen dioxide were 105 and 785 s, respectively. These are very similar to the values reported in [6]. …”
Section: Resultssupporting
confidence: 92%
“…Figure 7 shows the response of the sensors at both temperatures, which is better at 150 °C. S. Roso et al [6] reported an optimum operating temperature of 130 °C for a high-temperature grown In 2 O 3 (octahedral nanoparticles on top of an alumina substrate), which correlates with our results. When operated at the optimal operating temperature of 150 °C, response and recovery times (t90) for nitrogen dioxide were 105 and 785 s, respectively.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In order to obtain a gas sensor able to distinguish or being able to discriminate a particular gas from a mixture, a doping material can be introduced to the sensing layer structure to enhance or induce a change in the layer and subsequently obtain either a signal or a higher signal to a target gas. For this purpose, metal-oxide nanoparticles are used as dopant, as it has been demonstrated in our previous works, to perform such labor [1]. As AACVD is a flexible method to grow nanostructures we have successfully designed a 2 step procedure to grow and ensure the loading of dopants to the nanowires with noble metal nanoparticles such as Pt, Au and Pd [2].…”
Section: Introductionmentioning
confidence: 99%